HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN KEBERSIHAN ORGAN GENITALIA EKSTERNA SEBAGAI UPAYA PENCEGAHAN KEPUTIHAN PADA MAHASISWI FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS SUMATERA UTARA TAHUN 2015 - ria mistika; Sri Rahayu Sanusi; Asfriyati . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT Incidence of vaginal discharge mostly caused by candidosis vulvovagenitis because many women who do not know the cleaning the vaginal area, other causes are bacterial vaginitis and trichomonas vaginalis (Depkes RI, 2010). The habit of keeping and taking care of the cleanliness of external genitalia is an attempt to prevent the problem of sex organs one whiteness. However, misinformation regarding the treatment of external genital organs and a lack of awareness is still a problem of women, including female students. This study aims to determine the correlation between knowledge and attitude to the external genitalia hygiene measures for prevention of vaginal discharge in student of Public Health USU on 2015. This type of research is descriptive analytic. The study population was all female students public health USU class of 2013 as many as 757 people. Samples were obtained as many as 137 people. Then performed statistical tests with computer programs using the Chi-square test with α = 0,05. Results of research by bivariate analysis shows that there is a relationship between knowledge and action on the cleanliness of the external genitalia as prevention of vaginal discharge (p = 0.010) and attitude to the action on the cleanliness of the external genitalia as prevention whitish with (p = 0.027). From the results obtained, it is advisable to student of public health USU, as a student of public health so that more informed and read books about the cleanliness of the external genitalia that can motivate yourself to be more aware of reproductive health, especially how the cleanliness of external genitalia correct, prevention whitish and the dangers that occur when one cleans external genitalia.